Effect of allethrin exposure on the expression of YBX2 and JHDM2A genes in spermatogenesis of male rats (Rattus novergicus) strain wistar - Handayani, Putri; Rasyid, Rosfita; Ali, Hirowati (International Journal of Research in Medical Sciences, 2019)
Background: YBX2 and JHDM2A gene is important in spermatogenesis which acts as biomarkers of infertility. Allethrin chemicals widely used in mosquito and potentially toxic drugs that can damage DNA. The purpose of this study was to decide the effect of allethrin on decreasing YBX2 and JHDM2A gene expression on spermatogenesis of male white mice. Methods: This research is an experimental post-test randomized control group design. Twenty-eight rats were given exposure according to the experimental group is K (control), P1 (exposure 4hours), P2 (exposure 8hours), and P3 (exposure 12hours) for 30 days. Examination of YBX2 and JHDM2A gene expression from testicular tissue using real-time PCR with a relatively quantitative calculation method. Research implementation at Animal House and Biomedical Laboratory. Data analysis using one way ANOVA with a significant level of p<0.05. Results: The results of this study were found mean differences amount of YBX2 and JHDM2A gene expression. The mean expression of the control group YBX2 gene is 1.1376, P1: 0.8976, P2: 0.5504, and P3: 0.4512. While in JHDM2A gene control group was 1.7033, P1: 1,7025, P2: 0.6863, and P3: 0.4077. Results of statistical tests using one-way ANOVA is YBX2 (p = 0.010) and JHDM2A (p = 0.000). Conclusions: Based on the results of this study it was concluded that there was an allethrin effect on the decrease in YBX2 and JHDM2A gene expression in the Wistar Albino Rattus novergicus strain.